تحليل جغرافي للرؤية المستقبلية لقيم الاراضي السكنية في مدينة الكوت - Kazem Abbas Al-Shamry, Bassem; Dari Al-Saadoun, Abdul - Jalil (Journal of College of Education, 2022)
Abstract : The study showed the high values ​​of residential lands in all the neighborhoods of the city despite the inefficiency of the services provided in them, in addition to the insufficiency of housing projects to address the phenomenon of slums and reduce the problem of housing deficit according to the planning standards and statistical methods used by the study, while it showed a wide gap between the reality of land values Spatially housing and planning indicators, and the inequality of the spatial distribution of residential land, and in order for the residential use service to be highly efficient and in the best way, contribute to addressing the high values ​​of residential land and reducing the problems of slums and the housing deficit. Goal (2030)